Trends and transformations in world politics - Tüfekçi, Özgür; Dag, Rahman (Lexington Books, 2022)
"This book analyzes the state of global governance in the current geopolitical environment through the trends and transformations it is going through. It evaluates the main challenges and crises and discusses potential opportunities for global governance"--